Controlled release of curcumin from gelatin hydrogels by the molecular-weight modulation of an oxidized dextran cross-linker. (30th August 2023) - Yan, Shizhang; Wu, Siyu; Zhang, Jianxun; Zhang, Shuang; Huang, Yuyang; Zhu, Huaping; Li, Yang; Qi, Baokun
Graphical abstract: Highlights: Oxidized dextrans (ODex) with different aldehyde group contents are prepared. ODex is used as a green cross-linking agent for gelatin to obtain hydrogels. A high content of aldehyde groups leads to an enhanced degree of cross-linking. The composite hydrogels are thermally stable with excellent mechanical properties. Adjustment of the hydrogel characteristics allows the controlled release of curcumin. Abstract: Controlled drug delivery could minimize side effects while maintaining a high local dose. Herein, a hydrogel carrier was prepared by forming dynamic imine bonds between gelatin and oxidized dextran (ODex) of different molecular weights (Mw = 10, 70, and 150 kDa). The morphology, thermal stability, rheology, mechanical properties, and swelling properties of the hydrogels and the controlled release of curcumin were characterized. When dextran with a higher Mw was used, the ODex contained more aldehyde groups, which led to a higher degree of cross-linking, considerably shorter gel time, decreased hydrogel porosity, and well-controlled release of curcumin. In addition, the cross-linked hydrogels exhibited not only high thermal stability but also excellent mechanical properties. However, because the matrix was hydrophilic, the swelling properties of the hydrogels were not significantly affected by the Mw of ODex. These observations suggest an approach for designing nutrient delivery carriers with improved controlled release.